2015
DOI: 10.7764/psykhe.24.1.724
|View full text |Cite
|
Sign up to set email alerts
|

¿Pruebas Tradicionales o Evaluación Invisible a Través del Juego? Nuevas Fronteras de la Evaluación Cognitiva

Abstract: Esta investigación fue financiada por el Fondo Nacional de Desarrollo Científico y Tecnológico (FONDECYT) a través del proyecto 1110975 a cargo del primer autor. La participación de Marcela Tenorio en esta investigación fue posible gracias al apoyo de FONDECYT Postdoctoral 3031612. La correspondencia relativa a este artículo debe ser dirigida a Ricardo Rosas D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(27 reference statements)
0
10
0
2
Order By: Relevance
“…One study reported that children were individually tested in a single session in a quiet room in the school (Treiman et al 2006 ). Another study reported that the students were tested using a web‐based assessment (Rosas et al, 2015 ). Nearly half of the studies in the sample did not report the data collection procedures.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that children were individually tested in a single session in a quiet room in the school (Treiman et al 2006 ). Another study reported that the students were tested using a web‐based assessment (Rosas et al, 2015 ). Nearly half of the studies in the sample did not report the data collection procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The main goal of this study is to investigate the neuropsychological profile in different clinical populations through the Yellow Red and TENI assessment batteries, both in Tablet format, which evaluate different cognitive abilities related to EF and are within the paradigm of invisible evaluation through game (Rosas et al, 2015).…”
Section: Purposementioning
confidence: 99%
“…In addition, tasks should be transformed into games, to increase motivation and to facilitate capturing and maintaining the attention of those with NDDs. Games are a creative way to turn difficult problems into accessible tasks that such individuals can understand (Rosas & Ceric, 2011). If a technological platform is added to the game context, we have created a bridge between evaluator and the person being evaluated, one that motivates, supports activities, facilitates engagement and maintains attention.…”
Section: The Transformation Of Cognitive Assessmentmentioning
confidence: 99%
“…This paper aims to demonstrate why traditional tests are under crossfire because of problems that are inherent to their format (Rosas & Ceric, 2011) but also because of their most important theoretical limitation: the impossibility of tracing developmental trajectories with the measurements that they provide. Beyond this central issue, we also point to some minor difficulties and discuss them with reference to empirical data.…”
mentioning
confidence: 99%